Lactic beverages and yogurts labels commercialized in Curitiba, Paraná - Teider Junior, Pedro Irineu (2017)
The objective of this study was to verify whether the labels of packages of yogurts and dairy beverages marketed in supermarkets of Curitiba-PR were in accordance with the norms established by Ministry of Agriculture and Food Supply (MAPA). For this, we have evaluated 16 labels of yogurt and 13 labels of dairy beverages industrialized and under federal inspection. The items were classified into “according” and “nonconforming” or “does not apply”. The verification took place in 25 packages of yogurt and 31 packages of dairy drinks. All evaluated brands presented disagreementon the label. The highest incidence of inadequacies were the non-submission of the product name in conformity with the trademark (100% of the evaluated brands of both products), and absence of INS (International Numbering System for food additives) with 81.25% of absence in yogurt labels and 100% of absence in dairy drinks. We observe irregularities in the batch number of the products, date of manufacture and/or validity of the product, false or insufficient information, medicinal or therapeutic properties and absence of the information of the functions of the additives used. With this, one can conclude that the manufacturers are not obeying the norms established by the legislation.